Islamization of Science in Raji Al-Faruqi’s Thought, between The Fundamentalism Reflection and Construction of New Epistemological Knowledge - Badarussyamsi, Badarussyamsi (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
This article discusses more deeply and presents an exploration of the study of Ismail Raji al-Faruqi with his knowledge of the Islamization paradigm. This exploration is important considering that there are assessments that have not positioned al-Faruqi proportionally, for example al-Faruqi's ideas are considered as a general characteristic of religious fundamentalism, or as a representation of a marginal culture. The main problem to be answered is whether the idea of the Islamization of knowledge is a pure scientific project or is it only a theological response of religious fundamentalism? As a literature study, this article conducts an in-depth study of al-Faruqi's work, especially on the Islamization of knowledge. As for analyzing it, I use theories of knowledge paradigms or theories about the basics of knowledge. The research findings show that although it has religious content, al-Faruqi's idea of the Islamization of knowledge cannot be categorized as a representation of theological expression of religious fundamentalism. In contrast, al-Faruqi has academically designed a notion of knowledge as a critique of previous knowledge. In constructing his knowledge, al-Faruqi has fulfilled philosophical stages such as determining the object of study as the basis of his ontological study, and determining the framework of study as his epistemological basis. However, al-Faruqi's efforts still require follow-up from later scientists so that the idea of the Islamization of knowledge is truly realized to the fullest. Artikel ini mendiskusikan lebih dalam dan menyuguhkan eksplorasi kajian tentang Ismail Raji al-Faruqi dengan paradigma Islamisasi pengetahuannya. Eksplorasi ini penting mengingat adanya penilaian yang belum memposisikan al-Faruqi secara proporsional, misalnya gagasan al-Faruqi dinilai sebagai karakter umum fundamentalisme agama, ataupun merupakan representasi dari kultur yang marjinal. Masalah utama yang diangkat adalah apakah gagasan Islamisasi pengetahuan merupakan proyek ilmu pengetahuan murni ataukah hanya sebatas respon teologis dari fundamentalisme keagamaan? Sebagai sebuah penelitian literatur, artikel ini melakukan kajian mendalam terhadap karya al-Faruqi khususnya tentang Islamisasi pengetahuan. Adapun untuk menganalisisnya, saya menggunakan teori-teori paradigma pengetahuan ataupun teori tentang dasar-dasar pengetahuan. Temuan penelitian menunjukkan bahwa meskipun memiliki muatan keagamaan, gagasan Islamisasi pengetahuan al-Faruqi tidak dapat dikategorikan sebagai representasi dari ekspresi teologi fundamentalisme agama. Sebaliknya, al-Faruqi secara akademis telah merancang sebuah gagasan pengetahuan sebagai kritik dari pengetauan sebelumnya. Dalam mengkonstruksi pengetahuannya, al-Faruqi telah memenuhi tahapan-tahapan filosofis seperti penentuan objek kajian sebagai basis kajian ontologisnya, serta penentuan kerangka kajian sebagai basis epistemologisnya. Namun, upaya al-Faruqi masih memerlukan tindak lanjut dari ilmuan setelahnya agar gagasan Islamisasi pengetahuan ini benar-benar terealisasi secara maksimal.